REPELLENT ACTION OF SEVIN PLANT EXTRACTS AGAINST TROGODERMA GRANARIUM (COLEOPTERA : DERMESTIDAE) - DWIVED, S.C.; BAJAJ, MAMTA (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2000)
The pet. ether extract of species Cassia, Tridex, Parthenium, Dalbergia, Lawsonia, Eucalyptus, Aegle have been assessed for their repellent activity against Trogoderma granarium. Among these plant extracts cassia leaf extract exhibited highest repellent action whereas minimum repellent property was recorded in Aegle.